THE MECHANICAL CHARACTERISTICS OF THE CASTED INGOTS FROM THE STEEL OF TYPE 5XHM , RECEIVED BY CAST MOULDING INTO INGOT MOLD AFTER INDUCTION REMELT OF STEEL WASTE - V. N. Fedulov; V. E. Liventsev (Литьë и металлургия)
There is offered the technology of the cast instrument production by means of induction smelting using different metal discards as a base mixture. The given results of investigations prove the possibility of the cast instrument production and its application.